Oxygen metabolism abnormalities and high-altitude cerebral edema - Li, Zhi; Zhang, Jianping; Zhang, Xiaoxia; Jin, Qiaoying; Zheng, Xingxing; Mo, Li; Da, Zejiao (Frontiers in Immunology, 2025)
Hypobaric hypoxia is widely recognized as a prominent risk factor for high-altitude cerebral edema (HACE), which contributes to the exacerbation of multiple pathological mechanisms, including oxidative stress, mitochondrial dysfunction, disruption of blood−;brain barrier integrity, neuroinflammation, and neuronal apoptosis. Among these mechanisms, abnormalities in oxygen metabolism, including hypoxia, oxidative stress, and mitochondrial dysfunction, play pivotal roles in the pathophysiology of HACE. In this review, our objective is to enhance our comprehension of the underlying molecular mechanisms implicated in HACE by investigating the potential involvement of oxygen metabolism. Addressing aberrations in oxygen metabolism holds promise for providing innovative therapeutic strategies for managing HACE.